Poultry feed metabolizable energy determination using total or partial excreta collection methods - Dourado, LRB [UNESP]; Siqueira, JC [UNESP]; Sakomura, NK [UNESP]; Pinheiro, SRF [UNESP]; Marcato, SM; Fernandes, JBK [UNESP]; Silva, JHV [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2010)
The aim of this work was to compare the efficiency of total (TC) or partial (PC) collection excreta methods to determine metabolizable energy in poultry feeds. A number of 180 12- to 21-day-old broilers were distributed into two treatments of six replicates of 10 birds each. A reference-diet was formulated to supply broiler requirements, and the test-diets consisted of 60% of reference diets and 40% of corn or soybean meal. Celite was added at 1% to the diets as a marker. Excreta and diet samples were analyzed for dry matter, energy, nitrogen, and acid-insoluble ash (AIA). AME of corn determined by partial collection (PC) was higher (3544 kcal/kg) as compared to total collection (TC) (3133 kcal/kg). However, no difference were observed for soybean meal (1797 vs. 1821 kcal/kg) between both methods. Marker recovery rates in the excreta were 101, 111, and 96% for the basal-diet, and the test-diets with corn or soybean meal, respectively. This result indicates the importance of marker recovery rate in the excreta to evaluate feed AME and digestibility.
Keywords: Acid insoluble ash; AIA; Broiler; Digestibility; marker; partial collection method